Performance evaluation of five ELISA kits for detecting anti-SARS-COV-2 IgG antibodies. (January 2021) - Yassine, Hadi M.; Al-Jighefee, Hadeel; Al-Sadeq, Duaa W.; Dargham, Soha R.; Younes, Salma N.; Shurrab, Farah; Marei, Reham M.; Hssain, Ali Ait.; Taleb, Sara; Alhussain, Hashim; Al-Nesf, Maryam A.; Al-Khal, Abdullatif; et al.
Highlights: Performances of five commercial ELISA for detecting anti-SARS-CoV-2 IgG was evaluated. Samples were from diverse nationalities and the negative group contained seropositive samples for other HCoV. All assays showed low sensitivity during the early stages; however, it was greatly improved overtime. Lionex showed the highest specificity, followed by EDI and Dia.Pro, NovaTec, and lastly AnshLabs. Lionex demonstrated the best performance and does not cross-react with any other HCoV. Abstract: Objectives: To evaluate and compare the performances of five commercial ELISA assays (EDI, AnshLabs, Dia.Pro, NovaTec, and Lionex) for detecting anti-SARS-CoV-2 IgG. Methods: Seventy negative control samples (collected before the COVID-19 pandemic) and samples from 101 RT-PCR-confirmed SARS-CoV-2 patients (collected at different time points from symptom onset: ≤7, 8–14 and >14 days) were used to compare the sensitivity, specificity, agreement, and positive and negative predictive values of each assay with RT-PCR. A concordance assessment between the five assays was also conducted. Cross-reactivity with other HCoV, non-HCoV respiratory viruses, non-respiratory viruses, and nuclear antigens was investigated. Results: Lionex showed the highest specificity (98.6%; 95% CI 92.3–99.8), followed by EDI and Dia.Pro (97.1%; 95% CI 90.2–99.2), NovaTec (85.7%; 95% CI 75.7–92.1), then AnshLabs (75.7%; 95% CI 64.5–84.2). All ELISA kits cross-reacted with one anti-MERS IgG-positive sample, except Lionex. The sensitivity was low during the early stages of the disease but improved over time. After 14 days from symptom onset, Lionex and NovaTec showed the highest sensitivity at 87.9% (95% CI 72.7–95.2) and 86.4% (95% CI 78.5–91.7), respectively. The agreement with RT-PCR results based on Cohen's kappa was as follows: Lionex (0.89) > NovaTec (0.70) > Dia.Pro (0.69) > AnshLabs (0.63) > EDI (0.55). Conclusion: The Lionex and NovaLisa IgG ELISA kits, demonstrated the best overall performance.